Seedling growth performance and salinity tolerance of two rice (Oryza sativa L.) varieties under different priming treatments - Jammeh, Fatoumata (2018)
Salinity is the presence of dissolved salts in soil and it affects vast areas of agricultural land which is a threat to rice production. There is a need to develop new techniques in order to improve rice tolerance to salinity. The study aimed to evaluate the effects of different priming agents on seed germination and early seedling growth and performance under saline environments. The experiment was conducted using a Gambian (IR72402–B-25-3-1-B) and a Malaysian (MR219) rice varieties. In the first experiment, rice seeds were primed with choline and NaCl solutions and sown in sand medium with EC 0, 1, 2, and 3 dS m-1 for 14 days. Seed priming has improved the germination percentage and germination index, germination rate and seedling vigor index under saline environments. However, varieties responded differently with different priming concentrations and salinity levels. The IR72402 rice variety recorded 100% germination at the higher salinity level compared with MR219 variety. The 5 mM choline recorded the lowest mean germination time in both rice varieties. In the second experiment, one week old seedlings were primed in choline or NaCl solutions and grown in different concentration of NaCl solution for four weeks in polyethylene bags containing rice soil in the glasshouse. Rice seedlings exposed to salinity at 3 dS m-1 is detrimental to seedling growth. Seedling priming using 25 mM NaCl or5 mM choline improved seedling height when grown at 2 dS m-1 salinity level for both varieties.Similarly, seedling priming with 25 mM NaCl had higher shoot fresh and dry weights for both rice varieties when grown at 2 dS m-1salinity level.Seedling priming with 5 mM choline improved root traits of seedlings when grown under saline environments.Seedling priming with choline and NaCl increased the total chlorophyll content in both rice varieties with a maximum total chlorophyll content of ±5.82 mg cm-2.Following seedling priming, proline content in both rice varieties increased with increase in salinity level.Priming seedlings increased phosphorus, potassium,and nitrogen content in the shoot of both rice varieties under saline environment. The increase in N, P, and K explained increased seedling performance observed in this study. Primed seedlings had lower sodium content in the shoot relative to the control. This suggests that primed seedlings are able to reduce sodium uptake. This study indicates that NaCl as well as choline used as priming agents on seeds or seedlings can be a beneficial and practical approach to alleviate salinity problem in rice production.